Data from: Varying dataset resolution alters predictive accuracy of spatially explicit ensemble models for avian species distribution ... - Curry, Claire M.; Ross, Jeremy D.; Contina, Andrea J.; Bridge, Eli S. (Dryad, 2018)
Species distribution models can be made more accurate by use of new “Spatiotemporal Exploratory Models” (STEMs), a type of spatially explicit ensemble model (SEEM) developed at the continental scale that averages regional models pixel by pixel. Although SEEMs can generate more accurate predictions of species distributions, they are computationally expensive. We compared the accuracies of each model for 11 grassland bird species, and examined whether they improve accuracy at a statewide scale for fine and coarse predictor resolutions. We used a combination of survey data and citizen science data for 11 grassland bird species in Oklahoma to test a spatially explicit ensemble model at a smaller scale for its effects on accuracy of current models. We found that only four species performed best with either a statewide model or SEEM; the most accurate model for the remaining seven species varied with data resolution and performance measure. Policy implications: Determination of non-heterogeneity may depend on the ... : Zip file containing code and data for Curry et al. 2018Project: VARYING DATASET RESOLUTION ALTERS PREDICTIVE ACCURACY OF SPATIALLY EXPLICIT ENSEMBLE MODELS FOR AVIAN SPECIES DISTRIBUTION Accepted in Ecology and Evolution 12-Oct-2018. Versioning visible at: https://github.com/baeolophus/ou-grassland-bird-survey Please contact Claire M. Curry (cmcurry@ou.edu or curryclairem@gmail.com) about the *.R files or Jeremy Ross (jdross@ou.edu) about the point count and transect data. See README.txt for more information.CurryEtAl2018.zip ...